Finite element analysis of hydrogen diffusion/plasticity coupled behaviors of low-alloy ferritic steel at large strain. (3rd August 2017) - Cui, T.C.; Liu, P.F.; Gu, C.H.
Abstract: Hydrogen embrittlement is commonly considered as a typical failure mechanism for low-alloy ferritic steel under high pressure hydrogen environment. Currently, the hydrogen enhanced localized plasticity theory has been largely recognized for studying the hydrogen embrittlement mechanism by introducing the localized plastic flow and the hydrogen induced strain concept. However, the hydrogen induced strain and the plastic strain are often solved respectively in this theory, which may weaken the effect of hydrogen on the plastic deformation. The purpose of this paper is to propose a modified theoretical model from the microstructural level by emphasizing the coupling mechanism between the hydrogen diffusion and the plastic deformation at large strain, where the hydrogen induced strain is superimposed on the equivalent plastic strain instead of on the strain components. Fully implicit backward Euler algorithm by finite element analysis (FEA) under the corotational configuration is used to implement the proposed model, where the hydrogen induced strain is involved in the stress return process within each iteration, indicating a more direct interaction between them than existing works. FEA by using finite element software ABAQUS-UMAT subroutine is performed for the smooth tensile specimen and the notch specimen respectively under slow tensile strain rate loading and different hydrogen pressure. Developed direct coupling model is expected to further gain insight into the hydrogen embrittlement effect on the plastic deformation, especially at the trapping sites. Highlights: A hydrogen/plasticity coupled model for low-alloy ferritic steel is proposed. The equivalent hydrogen induced strain is added into the equivalent plastic strain. Direct coupling enhances the equivalent plastic strain and hydrogen diffusion. Hydrogen in trapping sites plays a leading role in promoting plasticity.